Perancangan Sistem Digitalisasi Pengelolaan Dana Desa - Askar Askar; Ratnawati Ratnawati; Mashud Mashud; Rustam Tahir (Jurnal Bumigora Information Technology (BITe), 2022)
This study aims to design a digitalization system for managing village funds. The method used in this research is Research and Development (R&D). The village fund management digitization system was developed using the Waterfall model. The data collection technique consists of 3, namely interviews, observation and literature study. the method used is the PIECES method (Perfomance, Information, Economic, Control, Effience, and Service). The needs analysis of the system to be built is grouped into three parts, namely hardware requirements and software requirements. system design with UML (Unified Modeling Language). The programming language used to develop applications is the PHP programming language. In addition, MySQL Database Management System (DBMS) is used for data storage. The test model implemented in the development of the village fund management digitalization system is the Black-box. the results of testing using blackbox on the features work properly and run well, it is proven from the test results that all are successful, there are no failed test results. A digitalization system for managing village funds that can provide solutions to obstacles in managing village funds that are carried out